'Nice to Meet You Again': When Heutagogy Met Blended Learning in Teacher Education, Post-Pandemic Era - Nurit Chamo; Liat Biberman-Shalev; Orit Broza (MDPI AG, 2023)
Heutagogy and blended learning (BL) are core concepts in the educational discourse post-COVID-19. Conducting a mixed-methods study, we investigate meeting points between heutagogy principles and BL in the context of curricular change in the academic timetable of teacher education college, where pre-COVID most courses have been taught face-to-face (F2F). At present, teacher educators and students meet F2F for three weeks, followed by a week of remote learning, combining synchronous and asynchronous pedagogies. Data have been collected by a closed-ended questionnaire and two focus groups, involving altogether 76 lecturers and 553 students. Findings indicate that heutagogy has been applied in all facets of BL, rather than only with online or digital technological components. This study explores a bottom-up growth of heutagogy expressions in BL at three meeting points. When the core facets of heutagogy principles have been identified, there has been a predominance of the students' agency and life-long learners, together with facets such as a non-linear learning and capability development that have been underrepresented. This study contributes to the research field of heutagogy in teacher education as it identifies the meaning and the way a structural change in the curriculum can constitute an accelerator and catalyst when implementing heutagogy in practice.